Respostas
respondido por:
3
Dados
f(x) = 2x + 1
g(x) = x^2 - x
f(g(-1)) = ?
Obs.: f(x) = y ; g(x) = y
g(x) = x^2 - x
g(-1) = x^2 - x
g(-1) = (-1)^2 - (-1)
g(-1) = 1 + 1
g(-1) = 2
f(g(-1)) = f(2) = ?
f(x) = 2x + 1
f(2) = 2.2 + 1
f(2) = 4 + 1
f(2) = 5
Logo, f(g(-1)) = 5
f(x) = 2x + 1
g(x) = x^2 - x
f(g(-1)) = ?
Obs.: f(x) = y ; g(x) = y
g(x) = x^2 - x
g(-1) = x^2 - x
g(-1) = (-1)^2 - (-1)
g(-1) = 1 + 1
g(-1) = 2
f(g(-1)) = f(2) = ?
f(x) = 2x + 1
f(2) = 2.2 + 1
f(2) = 4 + 1
f(2) = 5
Logo, f(g(-1)) = 5
Perguntas similares
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás